Analisis Tingkat Pemahaman Konsep Dan Pemecahan Masalah Fisika Siswa SMA Berbasis Strategi Metakognitif ISCoA (UPEJ Unnes Physics Education Journal, 2020)
Metacognition skills are needed in learning activities both in the learning process and in measuring learning outcomes. This study aims to analyze the level of understanding of high school students' physics concepts on waves and optics using the ISCoA metacognitive strategy (Identification, Selfregulation, Cognitive Assessment). The research was conducted through an online program, on 32 students of class XI IPA SMA Abu Bakar Yogyakarta as respondents using research and development methods. The instrument used in this study included a non-test instrument in the form of a modified MAI (Metacognitive Awareness Inventory) questionnaire which contained a statement of metacognitive awareness using the MAI reference, a test instrument in the form of 20 cognitive questions, a brief description of the reasoned category of measuring concept understanding and 4 questions to describe the problem solving category of the material. waves and optics. The results of this study were the metacognition ability in the developing category of 46.88%. The level of understanding of the concept of students is in the high category of 28.12%, the medium category of 46.88% and the low category of 25%. The level of problem solving ability of students in the poor category is 46.88%, and the high category is 12.5%.